THE EFFECT OF PROBLEMBASED LEARNING MODELTOWARD STUDENT LEARNING OUTCOME INDYNAMICELECTRICITY TOPIC AT CLASS XIN SMA NEGERI 1PERBAUNGANACADEMIC YEAR 2014/2015 - Yenni Manurung; Alkhafi Maas Siregar (INPAFI (Inovasi Pembelajaran Fisika), 2016)
ABSTRACT The objective of this research to know the significant difference of student learning outcome using Problem Based Learning Model in dynamic electricity topic at class X SMA Negeri 1 Perbaungan Academic Year 2014/2015.The type of research was quasi-experiment with the population is all of students at class X in odd semester consist of six classes.Sample of this research was obtained by cluster random sampling technique.The research instrument has  seven questions in essay form,the instrument tested validated.Research result obtained the average value of posttest in experiment class was 80.63 and 75.53for control class was higher than control class.It can be concluded that there was significant difference towards student learning outcomes using Problem based Learning Model.   Keywords : Problem Based Learning Model,Dynamic Electricity